Touching digital objects directly on multi-touch devices fosters learning about visual contents. (June 2021) - Brucker, Birgit; Brömme, Romy; Ehrmann, Amelie; Edelmann, Jörg; Gerjets, Peter
Abstract: Multi-touch devices are widely used in our daily lives and the field of education. Users touch the digital objects depicted on these devices directly with their hands and fingers. Prior research indicated that information processing is influenced by the proximity of the hand(s) to the displayed information: particularly visuospatial processing is fostered near the hands. Two experiments investigated this effect of hand proximity for learning about visuospatial information on multi-touch devices. Participants either touched digital objects (pictures of paintings with text labels) on a multi-touch table directly (near hand) or manipulated the objects indirectly by touching placeholders of the objects (far hand; hand proximity ). In Experiment 2, additionally, the interaction time with the displayed learning materials (time of contact between hands and objects/placeholders) was analyzed as continuous factor ( duration of touch ). In both experiments, learning outcomes were measured by recognition performance on the visuospatial and verbal aspects of the presented materials. Results of Experiment 1 showed – as expected – that visuospatial learning was fostered near the hands. Experiment 2 replicated this effect for visuospatial learning, when touch durations were sufficiently long. Hand proximity had no influence on verbal learning in both experiments. The results and implications for designing interactive multi-touch interfaces are discussed. Highlights: The proximity of the hands to information influences learning on multi-touch tables. Learning of visuospatial information is fostered near the hands. For learning of verbal information hand proximity had no influence. Duration of touch plays a role during interacting (touch-mind-hypothesis). Visuospatial information should be touched long enough on multi-touch devices.